Comparative histological and ultrastructural studies of thymus of indigenous and cross-bred broiler breeds of poultry of India - SHUKLA, MANSI; KARMORE, SHYAMSAGAR (The Indian Journal of Animal Sciences, 2024)
The present study was aimed to compare structure of thymus between the two poultry breeds, namely, Kadaknath and Narmada Nidhi. The aim was to understand the anatomical differences which could provide insights into how different breeds respond to diseases. The study involved histomorphological analysis of thymus tissue samples from 72 chicks (36 from each breed) that were divided into 6 groups with 6 birds in each group. The study results revealed that both poultry breeds exhibited similarities in the histology and ultrastructure of the thymus. This similarity is likely due to the Narmada Nidhi breed having a 25% genetic contribution from the Kadaknath breed.